Abscisic Acid-Stress-Ripening Genes Involved in Plant Response to High Salinity and Water Deficit in Durum and Common Wheat - Yacoubi, Ines; Gadaleta, Agata; Mathlouthi, Nourhen; Hamdi, Karama; Giancaspro, Angelica (Frontiers in Plant Science, 2022)
In the dry and hot Mediterranean regions wheat is greatly susceptible to several abiotic stresses such as extreme temperatures, drought, and salinity, causing plant growth to decrease together with severe yield and quality losses. Thus, the identification of gene sequences involved in plant adaptation to such stresses is crucial for the optimization of molecular tools aimed at genetic selection and development of stress-tolerant varieties. Abscisic acid, stress, ripening-induced (ASR) genes act in the protection mechanism against high salinity and water deficit in several plant species. In a previous study, we isolated for the first time the TtASR1 gene from the 4A chromosome of durum wheat in a salt-tolerant Tunisian landrace and assessed its involvement in plant response to some developmental and environmental signals in several organs. In this work, we focused attention on ASR genes located on the homoeologous chromosome group 4 and used for the first time a Real-Time approach to “in planta” to evaluate the role of such genes in modulating wheat adaptation to salinity and drought. Gene expression modulation was evaluated under the influence of different variables – kind of stress, ploidy level, susceptibility, plant tissue, time post-stress application, gene chromosome location. ASR response to abiotic stresses was found only slightly affected by ploidy level or chromosomal location, as durum and common wheat exhibited a similar gene expression profile in response to salt increase and water deficiency. On the contrary, gene activity was more influenced by other variables such as plant tissue (expression levels were higher in roots than in leaves), kind of stress [NaCl was more affecting than polyethylene glycol (PEG)], and genotype (transcripts accumulated differentially in susceptible or tolerant genotypes). Based on such experimental evidence, we confirmed Abscisic acid, stress, ripening-induced genes involvement in plant response to high salinity and drought and suggested the quantification of gene expression variation after long salt exposure (72 h) as a reliable parameter to discriminate between salt-tolerant and salt-susceptible genotypes in both Triticum aestivum and Triticum durum.